Managing the solid waste: recycling in Subang Jaya - Chenayah, Santha; Agamuthu, Pariatamby (2009)
Recycling is a relatively new exercise in Malaysia. Even though recycling has been introduced years back, lack of public awareness caused a slowdown in the progress of recycling exercise. Lack of sufficient recycling facilities or inappropriateness of the facilities’ location contributed further to the slowdown. Presently, about 19,000 tonnes (approaching 20,000 tonnes) of solid waste are being discarded daily. The Ministry of Housing and Local Government set a recycling goal to be 22% by 2020. In Malaysia, research is being done vastly on recycling but very few related to multicriteria. The objective of the paper is to study the status and the successfulness of recycling exercise in Subang Jaya, Malaysia. With an estimated area 161.8km² and an immense figure of 500,000 of people living in the vicinity of Subang Jaya City Council (SJCC), an estimated count of 350 tons of waste is produced on daily basis with each person contributing around 0.7kg waste per day, in accordance to a current study. Thus it demands a high management cost, with a staggering 50% out of the total tax collected by SJMC had to be allocated for the abovementioned matter. The present recycling rate of Subang Jaya is less than 1%. In this paper, we study ways to achieve the national recycling target by the year 2020. To this end, formulation and analysis of various strategies to raise the recycling rate are done. The evaluation of various strategies involves inherently qualitative criteria and imprecise data. Therefore, the outranking analysis which has been frequently used in such situations is employed. For ranking strategies, a new exploitation procedure based on eigenvector in a PROMETHEE context is proposed to evaluate the overall performance of recycling facilities in Subang Jaya. Analytic Hierarchy Process (AHP) is used to determine the weights based on the local officer and then various stakeholders in the decision process. Then, a generalized procedure in PROMETHEE analysis, a modified approach, is used to rank the alternatives to get an insight on recycling strategies. We proposed a new preference ranking procedure based on eigenvector using the “weighted” in- and out-preference flows of each alternative in the outranking analysis. The basic idea of the procedure proposed here is that it should be better to outrank a “strong” alternative than a “weak” one and, conversely, it is less serious to be outranked by a “strong” alternative than by “weak” one in a PROMETHEE context. It has a completely different interpretation with the AHP since the components of the valued outranking relation matrix are neither ratios nor reciprocal as in the AHP. A total of ten (10) strategies were formulated focusing on two main streams, namely, awareness creation and increasing recycling facilities. Results of our study show that both awareness creation and sufficient recycling facilities are necessary to increase the recycling rate in Subang Jaya. In order to achieve the national recycling target of 22% by the year 2020, intensive awareness creation programs are needed to create awareness among the residents of Subang Jaya. This has to be complemented with sufficient recycling facilities.